Editorial Notes Vol.8(1-2) - Alam, Mahmudul (Journal of Business and Technology (Dhaka), 2014)
DOI: http://dx.doi.org/10.3329/jbt.v8i1-2.18282 Journal of Business and Technology (Dhaka) Vol.8(1-2) 2013